A method for simulating spatial fates of chemicals in flowing lake systems: Application to phthalates in a lake. (1st April 2023) - Guo, Yaqi; Wang, Chenchen; Huang, Panpan; Li, Jing; Qiu, Chunsheng; Bai, Yaohui; Li, Chaocan; Yu, Jingjie
Highlights: A level IV fugacity model coupled with lake hydrodynamics is developed. The model was successfully applied to four PAEs in a flowing lake. PAEs in water and sediment have significant but different spatial heterogeneity. The distribution of PAEs in water depends on hydrodynamics and their primary source. PAEs accumulate in the sediments with slow-exchange overlying water. Abstract: In order to describe spatio-temporal distribution of chemicals in flowing lake systems, a dynamic multimedia fate model of chemicals with spatial differentiation was constructed by coupling the level IV fugacity model with lake hydrodynamics. It was successfully applied to four phthalates (PAEs) in a lake recharged by reclaimed water and its accuracy was verified. Results show that under the long-term influence of flow field, the distributions of PAEs in both lake water and sediment have significant spatial heterogeneity of 2∼5 orders of magnitude, but present different distribution rules, which was explained by analysis of PAE transfer fluxes. The spatial distribution of PAEs in the water column depends on hydrodynamic conditions and whether the primary source is reclaimed water or atmospheric input. Slow water exchange and flow speed promote the migration of PAEs from water to sediment, causing them to always accumulate in sediments far away from the recharging inlet. Uncertainty and sensitivity analysis show that the PAE concentrations in water phase are mainly affected by emission and physicochemical parameters, while those in sediment phase are also sensitive to environmental parameters. The model can provide important information and accurate data support for the scientific management of chemicals in flowing lake systems. Graphical abstract: Image, graphical abstract